Diagnóstico de la prevalencia de Brucella tipo lisa en perros (Canis lupus familiaris) de fincas del cantón Chone - Álvarez Álvarez, Carlos Andrés (2023)
The present study was developed with the objective of determining the prevalence and risk factors of Brucella lisa type in dogs (Canis lupus familiaris) in Chone canton farms, 103 dogs from several farms were evaluated by serological diagnosis Cart test (Rose Bengal) and slow agglutination serum in tube (SAT), and results related to breed, sex and age were analyzed, additionally an epidemiological cross-sectional study was applied to determine the risk factors associated with the transmission of this bacterium to dogs. The results show a prevalence level of 10 % with the Rose Bengal technique, 8 % with routine SAT and 1 % with the SAT titration response that determined the infectious phase of the disease. As for the predominant racial composition, the mongrel is found with 82 % of the positive cases, with a greater presence in female dogs with 59 % and a number of dogs concentrated in ages from 0 to 36 months representing 69 %. The risk factors that predispose the infection of Brucella lisa to dogs on the farms evaluated are the lack of medical controls, contact with possibly contaminated external environments and feeding with food derivatives and products from abortions of seropositive animals. It is concluded that there is a low prevalence of Brucella lisa in dogs from farms in Chone canton, which should be taken into account for a respective control by mitigating the risk factors detected.